Impulse Variability Following Increased Running Speed - shayeteh, Mohsen; Yousefian Molla, Razieh; Fatahi, Ali (Journal of Clinical Physiotherapy Research, 2021)
Introduction: Running usually happens at faster speeds than walking and faster the speed of running variability of some biomechanical parameters seems to be controversial. The purpose of this study was to investigate the impulse variability following increased velocity. Materials and Methods: twenty eight elite runners with body mass: 69.63±6.670 kg, age: 34.75±6.626 years and height: 175.96±6.74 cm participated in the present study. Kinetic data were measured at speeds of 2.5, 3.5, and 4.5 meters per second at a sampling frequency of 300 Hz when running on a treadmill on a force plate, and then the total impulse and mean impulse variables were extracted. To analyze the data at three different speeds, two-factor analysis of variance with repeated measures with a significant level of P<0.05 was used. Results: These results showed that with increasing speed in the stance phase, significant differences were obvious in average impulse by increasing speed (2.5 & 3.5- 2.5 & 4.5 and 3.5& 4.5 m/s). Also, significant difference was presented in total impulse between speeds of 3.5 and 4.5 m/s. Conclusion: It seems that a change in running speed causes a change in the momentum of the running support phase and increases with higher impulse speed.